Forest Genetics-Research and Application in Indian forestry-II - Dogma, P. D. (Indian Forester, 1981)
Genetic potential of indigenous species, genetic approach to tree improvement work in India, natural variation, identification, selection and conservation of geographic races and trees, cytological variation in oleoresin yield and quality in piles, and, importance of reproductive biology, was discussed in part one of this series The second part, presented here discusses genetic Control through seed, seed orchards, vegetative propagation haploidy and agamospermy and intra and interspecific hybridization potential of indigenous species. Suggestions on practical application of forest genetic in Indian forestry are given in the end.